Efforts to Improve Character Through Cak Bur Game - Ria Rizkia Alvi; Muhammad Jais; Aswandi Bahar (Universitas Muhammadiyah Ponorogo, 2022)
The behavior and character of the community and even children regarding noble values that are upheld and rooted in daily behavior. These values began to be eroded by foreign cultures that tend to be consumerism, individualistic, materialistic so that the character values are considered no longer important if they conflict with the goals to be achieved. Efforts to integrate and increase character values in the learning process can be done through traditional games with children, namely the Cak Bur game. This study aims to improve and enhance the character through cultural literacy of the traditional game of cak bur. This research uses action research which is carried out in two cycles. The subjects in this study were 2 groups of school-age children. The action taken is a game of cakbur to improve the child's character. Data were collected through observation, interviews, and documentation. The data analysis technique used is qualitative data analysis by reducing data, presenting data, and drawing conclusions. The results showed that the child's character increased by 8 characters with 9 characters that appeared during the game and were in good or increasing criteria. This development has reached the success criteria where the research is said to be successful if the characters that emerge from the cak bur game are 3 characters and there is an increase in the character of children in the cak bur game as many as 7 children. Thus, this research can be said to be successful